Strategic CRM Approaches for Strengthening Customer Loyalty and Satisfaction - Purwati, Suci; Novari, Eri (Islamicate Institute, 2023)
Customer Relationship Management (CRM) plays a pivotal role in enhancing customer satisfaction and loyalty by integrating strategy, technology, and relationship-building practices. This study investigates CRM as both a managerial philosophy and operational framework, focusing on how organizations strategically implement CRM to foster long-term customer relationships. Using a qualitative method through literature-based analysis, the study identifies key CRM strategies such as personalization, customer segmentation, multichannel communication, and cultural adaptation. It also examines how contextual factors—such as technological readiness, organizational culture, and industry-specific dynamics—shape CRM effectiveness. Findings suggest that CRM is most impactful when aligned with organizational goals and embedded in a culture of customer-centricity. The study contributes a conceptual synthesis that integrates relational and technological dimensions of CRM, offering theoretical refinement and practical guidance for organizations, particularly in emerging markets. The research highlights the need for context-sensitive CRM models and provides strategic implications for CRM deployment and performance enhancement.